Method of stand establishment and its impact on growth and yield dynamics of direct-sown and transplanted rice (Oryza sativa) cultivars under flood-prone lowland situations - GHOSH, A (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted at Cuttack during 1997 and 1998 to investigate the performance of direct-sown rice crop (Oryza sativa L.) following variable tiller removal and of subsequently established transplanted crop. Two tall, long-duration and photosensitive rice varieties, ’Amulya’ (improved selection) and ’Champaisali’ (local check) were established through direct seeding and also through transplanting employing either vegetative tillers or conventionally raised nursery seedlings. Vegetative tillers were removed in 3 proportions, 25, 50 and 75% of the total tillers available in the direct-sown stand. The tillers removed thereby were planted in the area equivalent to the direct-sown stand. An undisturbed direct-sown stand was also maintained for comparison. Crop stand following the removal of either 25 or 50% tillers achieved grain yield comparable with undisturbed stand which was however higher than the stand devoid of 75% tillers. As regards the transplanted stand, comparable grain yield was realized at the stand established with vegetative tillers available either from 50 or 75% of its removal; this was however, higher than that transplanted with 25% tillers. Importantly, grain yield in the stand with nursery seedling was comparable with tbe stand with tillers available from 25% removal during flood-prone year.